ANALISIS KUALITAS PELAYANAN PADA KESETIAAN PELANGGAN MELALUI PEMASARAN RELASIONAL PADA “UMM INN“ HOTEL PENDIDIKAN DI MALANG - Juliati, Ratih (Faculty of Economics and Business, University of Muhammadiyah Malang, 2011)
This research aims to seek an influence of service quality to the loyalty of the customer with relationship marketing.The study use a relationship marketing variable as intervening variable. Structural Equation Modeling (SEM) used to analyze the influence of service quality to customer loyalty through relationship marketing. The research show mention an influence of service quality to customer loyalty, service quality to relationship marketing, and relationship marketing to customer loyalty.